2019
DOI: 10.1107/s2056989019005966
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, Hirshfeld surface analysis and interaction energy and DFT studies of 3-{(2Z)-2-[(2,4-dichlorophenyl)methylidene]-3-oxo-3,4-dihydro-2H-1,4-benzothiazin-4-yl}propanenitrile

Abstract: The title compound, C18H12Cl2N2OS, consists of a dihydrobenzothiazine unit linked by a –CH group to a 2,4-dichlorophenyl substituent, and to a propanenitrile unit is folded along the S...N axis and adopts a flattened-boat conformation. The propanenitrile moiety is nearly perpendicular to the mean plane of the dihydrobenzothiazine unit. In the crystal, C—HBnz...NPrpnit and C—HPrpnit...OThz (Bnz = benzene, Prpnit = propanenitrile and Thz = thiazine) hydrogen bonds link the molecules into inversion dimers, enclos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The disintegration of two‐dimensional fingerprint contributed the inter and intera‐molecular interactions, usually can be found in the chemical structures [19–20,21,22] . In our study, powerful intermolecular associations observed within H−H as 30.8 % and 34.0 % for CPPAH and MBPAH , respectively (Figure 5).…”
Section: Resultssupporting
confidence: 59%
“…The disintegration of two‐dimensional fingerprint contributed the inter and intera‐molecular interactions, usually can be found in the chemical structures [19–20,21,22] . In our study, powerful intermolecular associations observed within H−H as 30.8 % and 34.0 % for CPPAH and MBPAH , respectively (Figure 5).…”
Section: Resultssupporting
confidence: 59%
“…Each point of the Hirshfeld surface contained two kinds of critical distances viz de and di, these were the distances from that point to the adjacent nucleus, outward and inward to the surface of molecule respectively. 42,43 Hirshfeld surface analysis for 1, 2 and 3 was done to estimate the strength of intermolecular interactions. The Hirshfeld surface structure for compounds 1, 2 and 3 are arranged in Fig.…”
Section: Hirshfeld Analysismentioning
confidence: 99%
“…[24] According to Bader, who proposed QT-AIM, this indicated a significant interaction between the atoms. [25] The non-covalent interactions are mainly characterized by their positive laplacian of density value (r 2 1(e/a 5 )) which indicates non-covalent interactions. The interactions with positive valued r 2 1 are listed in Table 2.…”
Section: Qt-aim Analysismentioning
confidence: 99%